Clinico-Pathological Study of Lymphangioma of the Head and Neck in Children - Omisakin, Olatunde Oluleke; Ayuba, Godwin Iko; Yates, Sannom; Zubair, Ramatu Aliyu; Ogunsina, Modupe Arinola; Dekah, Ibrahim Joseph (Medical Research and Its Applications Vol. 8, 2024)
Introduction: Lymphangiomas are uncommon congenital malformations of the lymphatic system that involve the skin and subcutaneous tissues. They are regarded as malformations that arise from sequestrations of lymphatic tissue that fail to communicate with the normal lymphatic system during embryogenesis. They are rare vascular malformations, Objective: To reveal the clinicopathologic features of head and neck lymphangiomas that underwent surgical resection in our health facility. Materials and Methods: This is a retrospective study of all cases of lymphangiomas of the head and neck in children treated in our health facility over a period from January 2010 to December 2023. Results: Ten cases were treated, 6 were males and 4 were female at a ratio of 3:2. The ages of the patients ranged from 3-months to 6-years. The lesions were located in the face, oral cavity and neck regions. Lymphangioma recurred in two cases: but no malignant transformation was noted on histology. Conclusion: Lymphangiomas in the head and neck region are not uncommon in children, therefore, neonatal screening of newborns for such anomalies is essential for early diagnosis and planning of treatment.